Un’analisi dei più recenti sviluppi della teoria del pecking order - Domenichelli, Oscar (Piccola Impresa / Small Business, 2007)
The original pecking order (PO) theory is not able to always justify the differences in financial policies of firms all over the world. However, the analysis of some recent and relevant papers enables us to delineate an “extended” PO theory (or “extended” PO) which can substantially explain the features of capital structure. In particular, the effects of specific factors are considered: new technologies, small and medium size of enterprises, capital markets of developed countries, transitional economies and innovative firm’s life cycle. These factors affect the information asymmetries between management/partners and other stakeholders and consequently lead to the following outcomes: a) they do not undermine the original PO (internal funds, debt, hybrid securities and lastly equity issues); b) they modify the original PO or its content; c) finally, they make possible the simultaneous presence of a particular form of the PO and other streams of literature on capital structure. Also firm control and institutional factors play a role in establishing the characteristics of the financial hierarchies being observed.